Co-localization of glucose oxidase and catalase enabled by a self-assembly approach: Matching between molecular dimensions and hierarchical pore sizes. (1st March 2019) - Zhuang, Wei; Huang, Jinsha; Liu, Xiaojing; Ge, Lei; Niu, Huanqing; Wang, Zhenfu; Wu, Jinglan; Yang, Pengpeng; Chen, Yong; Ying, Hanjie
Highlights: Efficient one-step production of gluconic acid was achieved. Adsorption capability of GOD and CAT was 24.18 and 14.33 mg·g −1, respectively. Co-localized GOD&CAT sustained the activity more than 90% after repeated utilization. The matching between dimensions of enzymes and hierarchical pore size of carriers are critical. Abstract: To achieve efficient one-step production of gluconic acid, cascade reactions of glucose oxidase (GOD) and catalase (CAT) have been advocated in the biocatalysis system. In this work, the methodology of co-immobilization of GOD and CAT was investigated in details for obtaining improved enzyme loading and activity. The maximum adsorption capability of GOD and CAT was 24.18 and 14.33 mg·g −1, respectively. The matching between dimensions of enzymes and hierarchical pore sizes of carriers are critical to the success of immobilization process. The simultaneous self-assembly on glutaraldehyde cross-linked mesoporous carriers exhibited favorable properties in comparison with sequential immobilization of GOD and CAT. The conversion of glucose under adequate air by co-localized GOD&CAT sustained the activity more than 90% after repeated utilization in the production of sodium gluconate and gluconic acid, suggesting that the co-immobilized GOD&CAT could be a promising catalyst for gluconate and gluconic acid production in some chemical and food industries.